Investigation of the Effects of an Inferior Vena Cava Filter and Captured Clot Size on the Hemodynamic Parameters in Non-Newtonian Turbulent Pulsatile Blood Flow - Jafar Moradicheghamahi; Muhammad Qasim; Sohrab Jafarpour; Hamed Farokhi (Applied Bionics and Biomechanics)
In this computational fluid dynamics (CFD)-based study, the effects of inferior vena cava (IVC) filter implantation on the risk of IVC thrombosis have been investigated using different hemodynamic parameters, including time-averaged wall shear stress (TAWSS), the oscillating shear index (OSI), and the relative residence time (RRT). The boundary conditions in this study have been based on physiological pulses. Additionally, the k–ω model and the Carreau model have been chosen to represent the turbulent flow regime and non-Newtonian blood, respectively. For this purpose, three blood clots with the largest cross-sectional diameters of 30%, 50%, and 70% of the filter diameter have been used. Capturing a small clot in the filter has the minimum effect on the hemodynamic parameters, while by increasing the size of the captured clot, OSI and RRT parameters increase in areas downstream of the filter on the wall. The presence of a filter and clot increases the risk of thrombosis. In the case of capturing large clots, there is the possibility of damage to endothelial cells or platelet activation. Captured clots lead to the formation of plaque and thrombus on the IVC wall. However, the possibility of thrombus growth on its surface is not negligible, particularly if larger clots are trapped in the filter.